Peer-mentors reflect on the benefits of mentoring: An autoethography - Booth, S.; Merga, Margaret; Mat Roni, S. (Informing Science Institute, 2016)
Many PhD candidates bring with them a wealth of knowledge and skills; however, these may not sufficiently prepare candidates to work with high autonomy on a project with often limited interaction with the wider research community. A peer-mentor program model, in which a mentor delivers dyadic and group support to higher degree by research students from different disciplines and backgrounds, has the potential to enhance candidates’ knowledge and skills. However, the mentors themselves can experience significant advantages, as peer-mentoring can also have a positive effect on the mentors’ research experience. In order to further understanding of the potential benefits of peer-mentoring for mentors, three researchers explore their experiences as peer-mentors through an autoethnographic framework. Through discussing their personal experiences as peer-mentors, the researchers identified a range of benefits for themselves. These benefits in-volved finding that peer- mentoring enhanced their own learning, fostered reflective practice, and provided current tertiary teaching and research support experience. Peer mentoring also gave them broad exposure to a breadth of disciplines, theories, and methods; provided project management insights; created opportunities for professional networking; supported their social needs; and gave them invaluable insight into other candidate/supervisor relationships. Their role in a peer-mentor model has shaped their experiences as PhD candidates and also informed their decisions after graduation.